The Influence of the Integration of Natural and Cultural Attractions on the Tourist Appeal of Istano Basa Pagaruyung - Winda Musdalifah; Fitria (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
As a major cultural tourism destination in West Sumatra, Istano Basa Pagaruyung has great potential because it combines natural beauty (green hilly landscapes, terraced rice fields, rivers, and Mount Marapi) with the beauty of Minangkabau culture (gonjong architecture, philosophical carvings, and local traditions). However, due to partial management, the natural attractions have not been fully utilized, potentially reducing tourist appeal and the site's sustainability. The purpose of this study is to examine how the integration of natural and cultural attractions affects the tourist appeal of Istano Basa Pagaruyung. Furthermore, this study also aims to develop a sustainable tourism management strategy based on community-based tourism (CBT) and eco-edutourism. A qualitative approach was used in the study, and data collection techniques were collected through field observations, in-depth interviews with managers and local community members, and literature review. The research results show that tourist satisfaction can be improved, destination image can be strengthened, and environmental and cultural preservation can be supported by the synergy of nature and culture reflected in the landscape around the palace, the Pacu Jawi tradition, Alu Katentong, and the local wisdom story